PRMT4 Is a Novel Coactivator of c-Myb-Dependent Transcription in Haematopoietic Cell Lines - STREUBEL, GUNDULA (My University, 2013)
Protein arginine methyltransferase 4 (PRMT4)–dependent methylation of arginine residues in histones and other chromatin- associated proteins plays an important role in the regulation of gene expression. However, the exact mechanism of how PRMT4 activates transcription remains elusive. Here, we identify the chromatin remodeller Mi2 a as a novel interaction partner of PRMT4. PRMT4 binds Mi2 a and its close relative Mi2 b , but not the other components of the repressive Mi2- containing NuRD complex. In the search for the biological role of this interaction, we find that PRMT4 and Mi2 a / b interact with the transcription factor c-Myb and cooperatively coactivate c-Myb target gene expression in haematopoietic cell lines. This coactivation requires the methyltransferase and ATPase activity of PRMT4 and Mi2, respectively. Chromatin immunoprecipitation analysis shows that c-Myb target genes are direct transcriptional targets of PRMT4 and Mi2. Knockdown of PRMT4 or Mi2 a / b in haematopoietic cells of the erythroid lineage results in diminished transcriptional induction of c-Myb target genes, attenuated cell growth and survival, and deregulated differentiation resembling the effects caused by c-Myb depletion. These findings reveal an important and so far unknown connection between PRMT4 and the chromatin remodeller Mi2 in c-Myb signalling.
PUBLISHED
Keywords: c-Myb target genes; c-Myb target genes